Evaluation of Pulmonary Hypertension Using 4D Flow MRI. Issue 1 (25th October 2021) - Cerne, John W.; Pathrose, Ashitha; Gordon, Daniel Z.; Sarnari, Roberto; Veer, Manik; Blaisdell, Julie; Allen, Bradley D.; Avery, Ryan; Markl, Michael; Ragin, Ann; Carr, James C.
Abstract : Background: Cardiac magnetic resonance imaging (MRI) is becoming an alternative to right heart catheterization (RHC) for evaluating pulmonary hypertension (PH). A need exists to further evaluate cardiac MRI's ability to characterize PH. Purpose: To evaluate the potential for four‐dimensional (4D) flow MRI‐derived pulmonary artery velocities to characterize PH. Study Type: Prospective case–control. Population: Fifty‐four PH patients (56% female); 25 controls (36% female). Field Strength/Sequence: 1.5 T; gradient recalled echo 4D flow and balanced steady‐state free precession cardiac cine. Assessment: RHC was used to derive patients' pulmonary vascular resistance (PVR). 4D flow measured blood velocities at the main, left, and right pulmonary arteries (MPA, LPA, and RPA); cine measured ejection fraction, end diastolic, and end systolic volumes (EF, EDV, and ESV). EDV and ESV were normalized (indexed) to body surface area (ESVI and EDVI). Parameters were evaluated between, and within, PH subgroups: pulmonary arterial hypertension (PAH); PH due to left heart disease (PH‐LHD)/chronic lung disease (PH‐CLD)/or chronic thrombo‐emboli (CTE‐PH). Statistical Tests: Analysis of variance and Kruskal–Wallis tests compared parameters between subgroups. Pearson's r assessed velocity, PVR, and volume correlations. Significance definition: P < 0.05. Results: PAH peak and mean velocities were significantly lower than in controls at the LPA (36 ± 12 cm/second and 20 ± 4 cm/second vs. 59 ± 15 cm/second and 32 ± 9 cm/second). At the RPA, mean velocities were significantly lower in PAH vs. controls (27 ± 6 cm/second vs. 40 ± 9 cm/second). Peak velocities significantly correlated with right ventricular EF at the MPA ( r = 0.286), RPA ( r = 0.400), and LPA ( r = 0.401). Peak velocity significantly correlated with right ventricular ESVI at the RPA ( r = −0.355) and LPA ( r = −0.316). Significant correlations between peak velocities and PVR were moderate at the LPA in PAH ( r = −0.641) and in PH‐LHD ( r = −0.606) patients, and at the MPA in PH‐CLD ( r = −0.728). CTE‐PH showed non‐significant correlations between peak velocity and PVR at all locations. Data Conclusion: Preliminary findings suggest 4D flow can identify PAH and track PVR changes. Level of Evidence: 1 Technical Efficacy: Stage 5